Preexposure to Objects that Contrast in Familiarity Improves Young Children's Lexical Knowledge Judgment. Issue 3 (2nd July 2016) - Hartin, Travis L.; Stevenson, Colleen M.; Merriman, William E.
ABSTRACT: The ability to judge the limits of one's own knowledge may play an important role in knowledge acquisition. The current study tested the prediction that preschoolers would judge the limits of their lexical knowledge more accurately if they were first exposed to a few objects of contrasting familiarity. Such preexposure was hypothesized to increase the salience of the metacognitive experiences that distinguish known from unknown kinds. These experiences include both the feeling of familiarity that a kind evokes and the amount of information about the kind that is retrieved spontaneously. In Experiment 1, 3- and 4-year-olds performed a matching task involving familiar and unfamiliar objects, then made lexical knowledge judgments about both objects and words. The accuracy of these judgments was predicted to exceed that of children who had not performed a matching task (Experiment 1) or who had performed one involving wooden blocks (Experiment 1) or only familiar objects (Experiment 2). This prediction was supported for children with vocabulary sizes typical of a younger 4-year-old but not for children with larger vocabularies. Additional analyses suggested that the primary source of error in the former group was insensitivity to both feeling of familiarity and amount of information retrieval. In contrast, the occasional errors made by the children with the larger vocabularies were likely due to lapses in executive control.